A sacralização de animais nas religiões afro-brasileiras: umas análise sob a perspectiva da ética utilitarista de Peter Singer - Medeiros, Saul de (My University, 2020)
This work aims to examine the problem of the sacralization of animals present in religions of African origin from the Nagô worldview, scanning together with the views of Peter Singer's classic Utilitarianism and Utilitarianism of preferences. Evidencing that the later purpose of this dissertation is to build the dialogue between Nagô religiosity and Peter Singer's philosophical theory, above all, to analyze how ethical issues can sensitize or agree with the freedom of the ritualistic practice of sacralization of non-human animals in religions of African matrix. Therefore, the entire theoretical basis of this text will transition into an interlocution between the ethical-philosophical aspects of Peter Singer's thought and the religious and cultural foundations of the Nagô tradition, inserted in Brazil from the process of the African diaspora.
Este trabalho tem como objetivo examinar a problemática acerca da sacralização de animais presente nas religiões de matriz africana a partir da cosmovisão Nagô, esquadrinhando juntamente com as visões do Utilitarismo clássico e Utilitarismo de preferências de Peter Singer. Evidenciando que o propósito postremo desta dissertação é construir o diálogo entre a religiosidade Nagô e a teoria filosófica de Peter Singer, sobretudo, para analisar como as questões éticas podem sensibilizar ou concordar com a liberdade da prática ritualística de sacralização de animais não-humanos nas religiões de matriz africana. Portanto, toda base teórica deste texto transitará em uma interlocução entre os aspectos ético-filosóficos do pensamento de Peter Singer e os fundamentos religiosos e culturais da tradição do povo Nagô, inserido no Brasil a partir do processo da diáspora africana.
Keywords: Singer, Peter, $d 1946-; Cultos afro-brasileiros; Animais; Ética; Utilitarismo; Afro-Brazilian cults; Animals; Ethics; Utilitarianism